Understanding the transmission of Mycobacterium ulcerans: A step towards controlling Buruli ulcer. - Anthony J Muleta; Rachael Lappan; Timothy P Stinear; Chris Greening (PLoS Neglected Tropical Diseases, 2021)
Mycobacterium ulcerans is the causative agent of Buruli ulcer, a rare but chronic debilitating skin and soft tissue disease found predominantly in West Africa and Southeast Australia. While a moderate body of research has examined the distribution of M. ulcerans, the specific route(s) of transmission of this bacterium remain unknown, hindering control efforts. M. ulcerans is considered an environmental pathogen given it is associated with lentic ecosystems and human-to-human spread is negligible. However, the pathogen is also carried by various mammals and invertebrates, which may serve as key reservoirs and mechanical vectors, respectively. Here, we examine and review recent evidence from these endemic regions on potential transmission pathways, noting differences in findings between Africa and Australia, and summarising the risk and protective factors associated with Buruli ulcer transmission. We also discuss evidence suggesting that environmental disturbance and human population changes precede outbreaks. We note five key research priorities, including adoption of One Health frameworks, to resolve transmission pathways and inform control strategies to reduce the spread of Buruli ulcer.